The Effect of Irradiation of a Titanium Alloy of the Ti–6Al–4V–Н System with Pulsed Electron Beams on Its Creep; Russian Physics Journal; Vol. 63, iss. 6 - Grabovetskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Mishin I. P. Ivan Petrovich; Zabudchenko O. V. Olga Vyacheslavovna (2020, 2020)
Title screen